Pensamientos: Cuaderno De Notas (Ediciones UC, 2018)
The artistic creation in Pedro Prado is complemented by his critical passion. In manifestos, chronicles and short essays, he questions himself and tries to give answers about the meaning of art, the role of the artist in society and the way of understanding the diversity of reality. The notes and notes gathered in these Pensamientos illuminate, with originality, the problems that concern the author.